SISTEM PENDUKUNG KEPUTUSAN KENAIKAN JABATAN PADA CV. BHANU SARANA JAYA MENGGUNAKAN METODE PROFILE MATCHING - Kartikabudi Pratama (LPPM Universitas Sains dan Teknologi Komputer, 2024)
CV. Bhanu Sarana Jaya is a company that operates in the field of selling livestock equipment, where livestock needs are growing rapidly for various products. Therefore, with the development of the company, the number of employees increases and a person's abilities in their field increase over time. However, due to system limitations, the current system still uses Ms. Word, this creates a lack of neatness in the promotion system and employee profile data collection and has an impact on reports and other activities. In this research, the author uses the Research and Development development model, namely the research method used to produce certain products and test the product's effectiveness. In designing the system, the author used the Dreamweaver CS5 application and MySQL database. Broadly speaking, Profile Matching is a process of comparing an employee's competencies into job competencies so that differences in competency (also called gaps) can be identified. The smaller the resulting gap, the greater the weight of the value, which means there is a greater opportunity for a prospective employee to be promoted. The aim of this system is to manage profiles and assessments which are requirements for promotion on a CV. Bhanu Sarana Jaya can run more effectively and efficiently so that it can improve the performance of the company's employees.